Ophiuroids (Echinodermata: Ophiuroidea) from Chamela bay, Jalisco, Mexico - Mireles-Velázquez, Daniel (2021)
Introduction: Chamela bay is located in the central portion of the coast from the Jalisco state, Mexico and is an important protected natural area. Despite this, the study of echinoderms in the area is incipient. Objective: To provide an updated checklist, descriptions of the species and a taxonomic key of the ophiuroids from Chamela bay. Methods: We collected specimens from 1998 to 2018, and also analyzed information from the literature and specimens deposited at international scientific collections from Chamela bay. Results: 19 species of ophiuroids are reported for the study area, distributed in two orders, seven families, and 11 genera. Seven of these correspond to new records for the area, one to a new record for Jalisco state, and two possibly represent new species. The biodiversity of ophiuroids in Chamela bay represents 15.2 % of ophiuroid species from the Mexican Pacific and 73 % from Jalisco. The number of known echinoderms in Chamela bay is increased to 48 species. Conclusions: The most complete checklist of the class Ophiuroidea in Chamela bay, Jalisco, is presented. The information provided can be used for other areas of the eastern Pacific. Chamela bay is important in terms of species richness due to its environmental heterogeneity and numerous islands.